"STEP" PROGRAM - A MEANS TO FIGHT OBESITY - Mihaela CHICOMBAN (Editura Universitatii Transilvania din Brasov, 2019)
The Step program is in line with the physical activities preferred to accelerate the process of reducing or maintaining body weight, these being some of the main problems the modern era is facing. Frequently, modern society comes up with a series of revolutionary programs as main focus, that can be used in the fitness world, programs that permanently contribute to improving the quality of life from all points of view.